Case Report of Thymoma Tumor Reduction Following Plasmapheresis. Issue 47 (November 2015) - Jiang, Wei; Yu, Qitao
Abstract : Abstract: For thymoma, multidisciplinary antitumor strategy is composed of surgery, chemotherapy, and radiotherapy. Meanwhile, ∼20% to 25% of patients with thymoma have myasthenia gravis and plasmapheresis is recommended for thymoma-associated myasthenia gravis. We report a case that a 40-year-old woman with thymoma experiencing tumor relapse after surgery showed significant response to plasmapheresis. This is the first case of thymoma responded to plasmapheresis, which may guide the study of the etiology and pathogenesis of thymoma.